Knowledge, attitude, and practice of e-cigarette use among undergraduate students: A comparative study between China and Indonesia - Ronald Hartono+; Chaofang Yan+; Ying Chen+; Boting Ma; Yaqi Deng; Yijia Sun; Pan Li; Yuye Dao; Rui Deng (Tobacco Induced Diseases)
Introduction The health risks associated with e-cigarettes are currently the focus of tobacco control efforts and public health initiatives. Given that China and Indonesia have the highest rates of adult smoking worldwide, it is imperative to gain a comprehensive understanding of e-cigarette prevalence among college students in these two nations.